AIME Problem 6

Geometry Level 4

With all angles measured in degrees, the product k = 1 45 csc 2 ( 2 k 1 ) = m n \prod_{k=1}^{45} \csc^2(2k-1)^\circ=m^n , where m m and n n are integers greater than 1. Find m + n m+n .

This problem is part of this set .


The answer is 91.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Note first that S = k = 1 45 sin 2 ( 2 k 1 ) = k = 1 90 sin ( 2 k 1 ) . S = \displaystyle\prod_{k=1}^{45} \sin^{2}(2k - 1)^{\circ} = \prod_{k=1}^{90} \sin(2k - 1)^{\circ}.

So then S = k = 1 179 sin ( k ) k = 1 89 sin ( 2 k ) = k = 1 179 sin ( k ) 2 89 k = 1 89 sin ( k ) cos ( k ) = S = \displaystyle\dfrac{\prod_{k=1}^{179} \sin(k)^{\circ}}{\prod_{k=1}^{89} \sin(2k)^{\circ}} = \dfrac{\prod_{k=1}^{179} \sin(k)^{\circ}}{2^{89} \prod_{k=1}^{89} \sin(k)^{\circ}\cos(k)^{\circ}} =

k = 90 179 sin ( k ) 2 89 k = 1 89 cos ( k ) = 1 2 89 \displaystyle\dfrac{\prod_{k=90}^{179} \sin(k)^{\circ}}{2^{89} \prod_{k=1}^{89} \cos(k)^{\circ}} = \dfrac{1}{2^{89}} since sin ( 90 + x ) = cos ( x ) . \sin(90 + x)^{\circ} = \cos(x)^{\circ}.

The given product is then just 1 S = 2 89 , \dfrac{1}{S} = 2^{89}, and so m + n = 2 + 89 = 91 . m + n = 2 + 89 = \boxed{91}.

Trevor Arashiro
Apr 21, 2015

Let T n T_n be the nth Chebyshev Polynomial where T n ( cos ( x ) ) = cos ( n x ) T_n(\cos(x))=\cos(nx)

Using the identity that cos ( x ) = cos ( 180 x ) \cos(x)=-\cos(180-x)

Looking at all the terms of 1 45 cos 2 ( 2 k 1 ) \displaystyle \prod_{1}^{45}\cos^2(2k-1) (we can do this because the identity sin ( x ) = cos ( 90 x ) \sin(x)=\cos(90-x) ) let each of these terms be a root of the polynomial f ( x ) f(x)

Thus we have ( x cos 2 ( 1 ) ) ( x cos 2 ( 3 ) ) ( x cos 2 ( 5 ) ) . . . ( x cos 2 ( 89 ) ) (x-\cos^2(1))(x-\cos^2(3))(x-\cos^2(5))...(x-\cos^2(89))

Let y 2 = x y^2=x . Then since y 2 cos 2 ( t ) = ( y cos ( t ) ) ( y + cos ( t ) ) y^2-\cos^2(t)=(y-\cos(t))(y+\cos(t)) we have

( y cos ( 1 ) ) ( y + cos ( 1 ) ) ( y cos ( 3 ) ) ( y + cos ( 3 ) ) . . . ( y cos ( 89 ) ) ( y + cos ( 89 ) ) (y-\cos(1))(y+\cos(1))(y-\cos(3))(y+\cos(3))...(y-\cos(89))(y+\cos(89))

Using the identity cos ( t ) = cos ( 180 t ) \cos(t)=-\cos(180-t)

( y cos ( 1 ) ) ( y cos ( 179 ) ) ( y cos ( 3 ) ) ( y cos ( 177 ) ) . . . ( y cos ( 89 ) ) ( y cos ( 91 ) ) (y-\cos(1))(y-\cos(179))(y-\cos(3))(y-\cos(177))...(y-\cos(89))(y-\cos(91))

Resubstituting for x

( x cos ( 1 ) ) ( x cos ( 179 ) ) ( x cos ( 3 ) ) ( x cos ( 177 ) ) . . . ( x cos ( 89 ) ) ( x cos ( 91 ) ) (\sqrt{x}-\cos(1))(\sqrt{x}-\cos(179))(\sqrt{x}-\cos(3))(\sqrt{x}-\cos(177))...(\sqrt{x}-\cos(89))(\sqrt{x}-\cos(91))

This polynomial is equivalent to T 90 ( x ) = 0 T_{90}(\sqrt{x})=0

We need to look at the constant term of the polynomial divided by lead coefficient as by vietas, this will yield the product of the roots which is what we're looking for.

Since 90 is not divisible by 4, our constant term will be 1 -1 . Also, the lead coefficient will be 2 89 2^{89} .

Thus our result is 1 2 89 \frac{1}{2^{89}} . However, since this is the product of cos \cos , we need to invert this to get our product of csc \csc so our answer here is 2 8 9 2^89 and m + n = 91 m+n=91

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...